Pengaruh Digital Marketing Terhadap Peningkatan Volume Penjualan Hasil Industri Rumahan Desa Cibodas - Melia Wida Rahmayani; Nita Hernita; Ayu Gumilang; Wulan Riyadi (Coopetition : Jurnal Ilmiah Manajemen, 2023)
The development of information technology is currently very rapidly affecting the community in supporting various business activities. Cibodas Village, one of the areas in Majalengka District, Majalengka Regency, West Java, has high regional potential in improving community welfare through home-based businesses made by the community itself. The purpose of this research is to find out the extent of the effectiveness of digital marketing in an effort to increase sales volume in order to get maximum profit. The method used is descriptive verification in which researchers describe the state of digital marketing in increasing sales volume. Correlation analysis is the analysis used in this study, partially testing the hypothesis to determine the effect. The conclusion in this study is that digital marketing has a positive and significant effect on sales volume, meaning that the benefits of digital marketing on sales volume are needed because it will increase or decrease sales volume.